Determiner omission in German prepositional phrases / Tibor Kiss. - Kiss, Tibor.
In this paper, we present an analysis of so-called determinerless PPs in German, i.e. prepositional phrases that allow singular count nouns to occur without an accompanying determiner, despite other rules in the grammar requiring the presence of the determiner. The analysis is based on annotated corpus data, which are fed into a statistical classifier (applying logistic regression). Superficially, the syntax of bare prepositional phrases is difficult to capture, and intuitions cannot be easily elicited. The analysis is based on data sets for two pairs of German prepositions: mit ‘with’ and ohne ‘without’, and über ‘over, above’ and unter ‘under, below’. The results of the classifiers applied to annotated data indicate which syntactic, morphological and semantic features are responsible for determiner omission. We are able to detect common properties of all four prepositions, as well as preposition-specific, and idiosyncratic properties. The apparently unsystematic conditions for determiner omission can be discerned by tracing the interaction of these properties.